2023
DOI: 10.3389/fimmu.2023.1276107
|View full text |Cite
|
Sign up to set email alerts
|

Clinical markers predict the efficacy of several immune checkpoint inhibitors in patients with non-small cell lung cancer in China

Yuxin Wang,
Jiahui Lu,
Chenxi Wu
et al.

Abstract: ObjectivesImmune checkpoint inhibitors (ICIs) are one of the most significant oncological treatment modalities as a result of the rapid advancement of immunotherapy. Programmed Cell Death-Ligand 1 (PD-L1) and tumor mutational burden (TMB) have emerged as key markers for predicting the efficacy and prognosis of ICIs in non-small cell lung cancer (NSCLC), and the predictive role of tumor-infiltrating lymphocytes (TILs) has also received significant attention. However, the prognosis of some individuals cannot be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Systematic reviews and meta-analyses have provided evidence that high baseline neutrophil count or high NLR were independently associated with adverse overall survival in various types of solid tumors ( 84 , 117 , 118 , 145 151 ), while normalization of post-treatment NLR was associated with improved survival ( 84 ). Moreover, systematic reviews and/or meta-analyses examining the correlation between NLR and outcomes in patients treated with immune checkpoint inhibitors have reported that higher NLR is a prognostic factor of worse disease control rate, objective response rate, progression-free survival, and/or overall survival in patients with head and neck squamous cell carcinoma ( 152 , 153 ), gastric carcinoma ( 154 , 155 ), melanoma ( 156 ), metastatic renal cell carcinoma ( 157 , 158 ), non-small cell lung carcinoma ( 159 ), hepatocellular carcinoma ( 160 ) and cancer patients in general ( 161 163 ). High post-treatment NLR has also been associated with poor survival outcomes in cancer patients treated with immune checkpoint inhibitors ( 162 ).…”
Section: A High Neutrophil-to-lymphocyte Ratio Is An Independent Prog...mentioning
confidence: 99%
“…Systematic reviews and meta-analyses have provided evidence that high baseline neutrophil count or high NLR were independently associated with adverse overall survival in various types of solid tumors ( 84 , 117 , 118 , 145 151 ), while normalization of post-treatment NLR was associated with improved survival ( 84 ). Moreover, systematic reviews and/or meta-analyses examining the correlation between NLR and outcomes in patients treated with immune checkpoint inhibitors have reported that higher NLR is a prognostic factor of worse disease control rate, objective response rate, progression-free survival, and/or overall survival in patients with head and neck squamous cell carcinoma ( 152 , 153 ), gastric carcinoma ( 154 , 155 ), melanoma ( 156 ), metastatic renal cell carcinoma ( 157 , 158 ), non-small cell lung carcinoma ( 159 ), hepatocellular carcinoma ( 160 ) and cancer patients in general ( 161 163 ). High post-treatment NLR has also been associated with poor survival outcomes in cancer patients treated with immune checkpoint inhibitors ( 162 ).…”
Section: A High Neutrophil-to-lymphocyte Ratio Is An Independent Prog...mentioning
confidence: 99%